Affective Meaning Through Metaphorical Language In Selected Ost of “The Greatest Showman” - Annisya Fajriati; Maria Theodora Ping; Yuni Utami Asih (E3L: Journal of English Language Teaching, Linguistics, and Literature, 2023)
The aim of this study is to categorize metaphor and to analyze the affective meaning of selected song of “The Greatest Showman” Movie which are “Come Alive” and “This Is Me”. It is a qualitatve study using content analysis to analyze the data based on Lakoff and Johnson (1980) theory for types of metaphors and Leech (1974) for affective meaning theory. There are 34 data that are analyzed which consist of 15 orientational, 14 ontological and 5 structural metaphors. Both of “Come Alive” and “This Is Me” showed similarities meaning to convey which is about trust and the process of self-acceptance in living life without having to worry about other people’s view